Controllable FRET processes towards ratiometric Fe3+ ion sensor of pseudo [3]rotaxane containing naphthalimide-based macrocyclic host donor and multi-stimuli responsive rhodamine-modified guest acceptor. (January 2022) - Cuc, Tu Thi Kim; Nhien, Pham Quoc; Khang, Trang Manh; Chen, Hao-Yu; Wu, Chia-Hua; Hue, Bui Thi Buu; Li, Yaw-Kuen; Wu, Judy I.; Lin, Hong-Cheu
Abstract: A multi-stimuli responsive pseudo [3]rotaxane NI-DBC/RB-DBA was composed of a green-emissive (λem  = 530 nm) naphthalimide-based macrocyclic host and a turn-on red-emissive (λem  = 595 nm) rhodamine-based guest towards Fe 3+ ion, which illustrated interesting photo-physical properties in dioxane/H2 O (4:6, v/v) solutions. Due to the chelation-induced ring unfolded form of red-emissive rhodamine unit upon the addition of Fe 3+ ion, mono-fluorophoric pseudo [3]rotaxane NI-DBC/RB-DBA could be transformed into bi-fluorophoric pseudo [3]rotaxane NI-DBC/RB-DBA-Fe 3+ to reveal the Förster resonance energy transfer (FRET) process, which could be further identified by time-resolved photoluminescence (TRPL) measurements to obtain a higher energy transfer efficiency of 45.4% than that (21.1%) of its analogous mixture without host-guest interactions. Regarding pH effects, both pseudo [3]rotaxane systems NI-DBC/RB-DBA and NI-DBC/RB-DBA-Fe 3+ could also be employed as pH sensors in acidic (pH = 1–6) and basic (pH = 8–12) conditions, respectively. Moreover, the pH range of 6–8 could be appropriate to maintain excellent sensing capabilities of pseudo [3]rotaxane NI-DBC/RB-DBA to detect Fe 3+ ion. Accordingly, pseudo [3]rotaxane NI-DBC/RB-DBA could show the FRET-ON sensing behaviour towards Fe 3+ ion, which was attributed to the turn-on red-emissive rhodamine-functionalized RB-DBA acceptor. Owing to the best FRET process and ratiometric fluorescence of bi-fluorophoric pseudo [3]rotaxane NI-DBC/RB-DBA-Fe 3+ after Fe 3+ ion detection, pseudo [3]rotaxane NI-DBC/RB-DBA provided a prominent limit of detection (LOD) value of 39.01 nM, which was further proceeded as simple test strips towards Fe 3+ ion recognition and applied to the detection of Fe 3+ ion in various pristine water samples. Therefore, the developed pseudo [3]rotaxane with host-guest interactions has been well designed and constructed to utilize FRET-ON processes as a novel Fe 3+ ion sensor. Graphical abstract: Image 1 Highlights: A novel FRET-based pseudo[3]rotaxane involving the naphthalimide host donor and rhodamine guest acceptor was fabricated. Multi-stimuli responsive properties of the pseudo[3]rotaxane were investigated under various pH values and metal ions. After Fe 3+ ion coordination, the pseudo[3]rotaxane revealed a FRET-ON process with a high energy transfer efficiency. The designed pseudo[3]rotaxane could be employed to detect Fe 3+ ion in various pristine water samples by simple test strips.